2013
DOI: 10.1016/j.ihj.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of leukotriene B4 and thromboxane B2 distinguish chest pain of cardiac and non cardiac origin

Abstract: The measurement of LTB4 and TXB2 levels may therefore be useful to distinguish the chest pain leading to MI from that of non cardiac in origin and for the management of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Leukotrienes are important multifunctional mediators of inflammation and promote neutrophil chemotaxis and adherence to capillary walls [ 48 ]. LTB4 is expressed on leucocytes after myocardial IRI [ 36 ], gets elevated in plasma in the course of myocardial infarction [ 42 ] and has been shown to be able to discriminate between cardiac and non-cardiac chest pain [ 26 ]. Coversin has an internal binding pocket capturing LTB4 and C5-inhibition prevents LTB4 formation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leukotrienes are important multifunctional mediators of inflammation and promote neutrophil chemotaxis and adherence to capillary walls [ 48 ]. LTB4 is expressed on leucocytes after myocardial IRI [ 36 ], gets elevated in plasma in the course of myocardial infarction [ 42 ] and has been shown to be able to discriminate between cardiac and non-cardiac chest pain [ 26 ]. Coversin has an internal binding pocket capturing LTB4 and C5-inhibition prevents LTB4 formation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…When measured within the first 24 hours of MI it was elevated also when compared with UA, stable CAD and non-CAD patients. In two studies the level of LTB 4 , when measured in blood among patients with MI was more than double of that in healthy controls [21,22]. It was also shown that LTB 4 can be released by ionomycin in the blood more in the group of patients with a history of MI than in healthy people [23].…”
Section: Acute Coronary Syndromementioning
confidence: 99%